Wireless charging scheme for medium power range application systems - D Karthikeyan; Sayon Koley; Mayukh Bagchi; Avijit Bhattacharya; K Vijayakumar (International Journal of Power Electronics and Drive Systems (IJPEDS), 2020)
Wireless power transmission (WPT) has attracted a wide variety of subjects in various disciplines and has also become a highly active research field due to its capacity to facilitate charging systems. Wireless power transmission will be compulsory to use soon as this technology enables electrical energy to be transmitted from a power source to an electrical load over an air gap without connecting wires. Wireless power transmission has been developed in the low power (1W to 10W) and high power (100W-500W) region. While the low power region development focuses on powering medical transplants and mobile charging, the higher end of the power spectrum is being developed for the electric vehicle (EV) applications. However medium power range (10W to 100W) is relatively unexplored due to lack of proper applications. The commercial WPT scheme is mainly used for the charging of lithium-ion batteries. Sensitive medium power loads like Lithium Polymer (LiPo) batteries do not have a wireless modular charging system. This paper discusses a proposed scheme for wireless charging of medium-range loads. LiPo batteries are used as the targeted charging load. A minimalistic approach has been considered while designing the electronics for efficiency improvement and a compact, modular scheme. The proposed scheme has been developed for drone and robotics applications and the results are validated.